Bone Regeneration: Novel 3D Hybrid Nanofiber Aerogels Coupled with BMP‐2 Peptides for Cranial Bone Regeneration (Adv. Healthcare Mater. 10/2018). Issue 10 (May 2018) - Weng, Lin; Boda, Sunil Kumar; Wang, Hongjun; Teusink, Matthew J.; Shuler, Franklin D.; Xie, Jingwei
Abstract : In article1701415, Jingwei Xie and co‐workers report the fabrication of novel three‐dimensional (3D) hybrid nanofiber aerogels composed of electrospun PLGA‐collagen‐gelatin (PCG) and Sr‐Cu co‐doped bioactive glass (BG) fiber segments, with incorporation of heptaglutamate E7 domain specific BMP‐2 peptides, through calcium binding. Their potential applications in healing a critical‐sized cranial bone defect is reported.